Pengaruh Modal Usaha, Inovasi Produk, dan Strategi Pemasaran Terhadap Persepsi Profitabilitas Pelaku UMKM Kuliner di Wilayah Pekalongan - Indonesia, Dini Kharisatul Khabibah; Rokhman, Nur; Dini Kharisatul Khabibah; Nur Rokhman; Titik Rianawati (LPPM Universitas Sains dan Teknologi Komputer, 2025)
UMKM in Indonesia have an important role in economic growth, as well as being able to absorb labor, and distribute development results. The purpose of this study was to determine the effect of business capital, product innovation, and marketing strategies on the perception of profitability of culinary UMKM actors in the Pekalongan area. The population in this study were culinary UMKM actors in the Pekalongan area. The sampling technique was purposive sampling so that 95 respondents were obtained. The questionnaire was distributes via Google Form and direct distribution to culinary UMKM actors in the Pekalongan area and measured on a Likert scale 1-5. The collected data were processed using Multiple Linear Regression. The results showed that business capital, product innovation, and marketing strategies had a partial and simultaneous effect on the perception of profitability of culinary UMKM actors in the Pekalongan area.